2004
DOI: 10.1021/bi049529p
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Derived Metabolites in Mouse Neuroblastoma N18TG2 Cells

Abstract: Oleamide is an endogenous sleep-inducing lipid that has been isolated from the cerebrospinal fluid of sleep-deprived mammals. Oleamide is the best-understood member of the primary fatty acid amide family. One key unanswered question regarding oleamide and all other primary acid amides is the pathway by which these molecules are produced. One proposed pathway involves oleoyl-CoA and N-oleoylglycine as intermediates: oleic acid --> oleoyl-CoA --> N-oleoylglycine --> oleamide. The first and third reactions are kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 42 publications
(77 reference statements)
3
54
0
1
Order By: Relevance
“…Arafat et al [93,106]. A melding of the two proposed pathways could also lead to PFAMs: first the cytochrome c-mediated production of the N-fatty acylglycine followed by PAM oxidation to the corresponding PFAM.…”
Section: Primary Fatty Acid Amidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Arafat et al [93,106]. A melding of the two proposed pathways could also lead to PFAMs: first the cytochrome c-mediated production of the N-fatty acylglycine followed by PAM oxidation to the corresponding PFAM.…”
Section: Primary Fatty Acid Amidesmentioning
confidence: 99%
“…FAAH will hydrolyze the N-acyltaurines and N-arachidonoylglycine to the corresponding fatty acid and amino acid [33,76], but the other N-acylamino acids are not degraded by FAAH [77]. We have shown that N-acylglycines are biosynthetic precursors to the PFAMs using purified PAM [72] and in PAM-expressing neuroblastoma cells [93][73] [92][E1]. Marnett and co-workers have found that the N-arachidonoylamino acids are substrates for lipoxygenase and cyclooxygenase in vitro [94,95], pointing either to a mechanism for the inactivation of the N-arachidonoylamino acids or for the formation of other bioactive, oxidized amino acid conjugates.…”
Section: N-acylamino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive efforts of this and other laboratories have failed to identify the key enzyme for generating N-oleoylglycine. Nevertheless, the production of N-oleoylglycine by a recombinant bile acid conjugating enzyme [22] and by cultured neuroblastoma cells [23] indicate the feasibility for a PAM-based mechanism for the generation of oleamide in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The approaches currently available rely upon complex gas chromatographic-mass spectral procedures [16,23,24] which are cumbersome and expensive. To address these limitations we have developed a highly specific enzyme-linked immunosorbant assay (ELISA) for measuring blood levels of oleamide.…”
Section: Introductionmentioning
confidence: 99%